Neurobiological substrates of altered states of consciousness induced by high ventilation breathwork accompanied by music - Amy Amla Kartar; Toru Horinouchi; Balázs Örzsik; Brittany Anderson; Lottie Hall; Duncan Bailey; Sarah Samuel; Nati Beltran; Samira Bouyagoub; Chris Racey; Yoko Nagai; Iris Asllani; et al. (PLoS ONE, 2025)
The popularity of breathwork as a therapeutic tool for psychological distress is rapidly expanding. Breathwork practices that increase ventilatory rate or depth, facilitated by music, can evoke subjective experiential states analogous to altered states of consciousness (ASCs) evoked by psychedelic substances. These states include components such as euphoria, bliss, and perceptual differences. However, the neurobiological mechanisms underlying the profound subjective effects of high ventilation breathwork (HVB) remain largely unknown and unexplored. In this study, we investigated the neurobiological substrates of ASCs induced by HVB in experienced practitioners. We demonstrate that the intensity of ASCs evoked by HVB was proportional to cardiovascular sympathetic activation and to haemodynamic alterations in cerebral perfusion within clusters spanning the left operculum/posterior insula and right amygdala/anterior hippocampus; regions implicated in respiratory interoceptive representation and the processing of emotional memories, respectively. These observed regional cerebral effects may underlie pivotal mental experiences that mediate positive therapeutic outcomes of HVB.